Timing of Androgen Deprivation Treatment for Men with Biochemical Recurrent Prostate Cancer in the Context of Novel Therapies. Issue 3 (18th September 2021) - Marshall, Catherine Handy; Chen, Yongmei; Kuo, Claire; Cullen, Jennifer; Jiang, Jiji; Rosner, Inger; Markowski, Mark; McLeod, David G.; Trock, Bruce J.; Eisenberger, Mario A.
Abstract : Abstract : Purpose: There were 3 recent U.S. Food and Drug Administration approvals for drugs to be used in nonmetastatic castration resistant prostate cancer, a state that arises from the unproven start of continuous androgen deprivation therapy (ADT) for biochemical recurrent prostate cancer (BCR), before metastatic disease is evident. This report examines the outcome of men with BCR who defer ADT until time of metastasis. Materials and Methods: Retrospective review of men diagnosed with clinically localized prostate cancer who underwent radical prostatectomy at Johns Hopkins Hospital and Walter Reed National Military Medical Center and developed BCR with a prostate specific antigen doubling time of not more than 10 months (806 patients). The primary end points were metastasis-free survival and overall survival from time of local treatment among men who delayed ADT until time of metastasis. Results: The median metastasis-free survival of men with BCR and a prostate specific antigen doubling time <6 months and 10 months who delay ADT until metastasis is 144 months (95% CI 48–not reached) and 192 months (95% CI 72–not reached), respectively, with a median overall survival of 168 months (95% CI 96–276 months) and 204 months (95% CI 120–276), respectively. Conclusions: Metastasis-free survival and overall survival of men with BCR who delay hormone therapy is long. This underscores the need to reevaluate when to start primary ADT in this patient population.